Tourism Accounting Information Systems For Evidence-Based Governance And Regional Economic Resilience: A Qualitative Case Study Of Pangandaran Regency: Sistem Informasi Akuntansi Pariwisata Untuk Tata Kelola Berbasis Bukti Dan Resiliensi Ekonomi Daerah: Studi Kasus Kualitatif Di Kabupaten Pangandaran - Nia Ramadani; Iqbal Lhutfi; Harpa Sugiharti (Jurnal Pendidikan Akuntansi Indonesia, 2026)
Pangandaran Regency relies heavily on tourism, yet seasonal demand, short visitor stays, and fragmented accounting information constrain evidence-based governance and regional economic resilience. This study examines how tourism accounting information systems support governance and economic resilience in Pangandaran Regency. A qualitative case study was undertaken using in-depth interviews with two key informants, supported by observations and documentary analysis. The findings indicate that integrating tourism revenue, accommodation occupancy, visitor, and local economic information improves inter-agency coordination, policy formulation, and tourism performance monitoring. Rather than functioning solely as administrative records, tourism accounting information serves as strategic evidence for public-sector decision-making. Based on these findings, the study proposes a preliminary conceptual model linking tourism accounting information systems, evidence-based governance, and regional economic resilience. The study contributes to the accounting information systems literature by demonstrating the strategic role of integrated accounting information in supporting public-sector governance within tourism-dependent regions.